2016
DOI: 10.1039/c5tb02054a
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and optimization of pH-responsive polymer nanoparticles for drug delivery to oral biofilms

Abstract: We previously reported on cationic, pH-responsive p(DMAEMA)-b-p(DMAEMA-co-BMA-co-PAA) block copolymer micelles with high affinity for dental and biofilm surfaces and efficient anti-bacterial drug release in response to acidic pH, characteristic of cariogenic (tooth-decay causing) biofilm microenvironments. Here, we show that micelle pH-responsive behaviors can be enhanced through alterations in corona:core molecular weight ratios (CCR). Although similarly stable at physiological pH, upon exposure to acidic pH,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
100
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(109 citation statements)
references
References 54 publications
8
100
0
1
Order By: Relevance
“…80 These observations reveal further insights into the NP/drug interaction, and although not necessary for bone fracture healing, it provides further application of NPs where pH-responsive release is beneficial, such as drug delivery for cancer and acidic milieus of biofilms. 81 …”
Section: Resultsmentioning
confidence: 99%
“…80 These observations reveal further insights into the NP/drug interaction, and although not necessary for bone fracture healing, it provides further application of NPs where pH-responsive release is beneficial, such as drug delivery for cancer and acidic milieus of biofilms. 81 …”
Section: Resultsmentioning
confidence: 99%
“…Then Zhou and co-workers optimized the nanoparticles by alterations in core molecular weight ratios (CCR) based on previous studies. The results showed that farnesol loaded nanoparticles with higher CCR, had enhanced pH-responsive drug release and thus exhibited greater antibiofilm efficacy in situ [158]. Behrens also reported chlorhexidine loaded nanoporous silica nanoparticles with the pH-activated release [205].…”
Section: The Stimuli-responsive Dds For Oral Infectious Diseasesmentioning
confidence: 91%
“…Some periodontitis related microbiota have been reported closely related to peri-implants diseases such as Prevotella intermedia (P. intermedia), A. actinomycetemcomitans, P. gingivalis, T. denticola, and T. forsythia. What's more, S. aureus, Candida albicans (C. albicans) have also been detected [156][157][158].…”
Section: Dds For Peri-implantitismentioning
confidence: 99%
“…These microspheres provide greater control over release versus scaffolds simply impregnated with antibacterial proteins [53]. Additionally, dental biofilms, which also present an acidic environment, were treated with pH-responsive diblock copolymer nanoparticles containing anti-biofilm agents [54,55]. At physiological pH (7.2), 50% of loaded drug was released within 15 h, while at acidic pH (4.5), 50% of loaded drug was released within 7 h. This approach may be useful in combination with or used in lieu of antibiotics to prevent biofilm colonization during bone regeneration [56].…”
Section: Controlled Drug Delivery To Bonementioning
confidence: 99%